(untitled) (Journal of Fatima Jinnah Medical University, 2026)
Background: Pregnant women are more susceptible to COVID-19 disease with increased risk of poor prognosis. The aim of study was to assess the fetomaternal outcomes in COVID-19 positive pregnant patients and compare them with COVID-19 negative pregnant patients. Methods: This prospective cohort study was conducted at Sir Ganga Ram Hospital Lahore from 15 May 2020 to 15 August 2020. Nasopharyngeal swabs from 98 pregnant women were screened for SARS-CoV-2 infection by RT-PCR. All pregnant women with and without COVID-19 were followed up for adverse maternal, fetal and neonatal outcomes. Crosstabs and logistic regression analyses were done to determine the risk of adverse maternal, fetal and neonatal outcomes. Results: Among 98 pregnant women, 47 (48.0%) were COVID-19 negative and 51 (52.0%) were COVID-19 positive. Incidence of maternal death was 20 (20.4%), abortion 47 (48.0%), stillbirth 12 (12.2%), low birth weight 14 (35.9%), and neo-natal ICU admission and death 5 (12.8%) each. After adjustment for maternal age, gestational age and parity, COVID-19 positivity showed statistically significant association and higher risk of adverse maternal outcomes (OR=2.8, p=0.057). However, COVID-19 positivity was not associated with adverse fetal outcomes (OR=0.6, p=0.328). Gestational age <28 weeks demonstrated significant association and higher risk of adverse fetal outcomes (OR=19.9, p=0.005). Conclusion: In conclusion, this study highlights that COVID-19 significantly increases the risk of adverse maternal outcomes, though it does not show a strong link to fetal complications. These findings emphasize the need for careful prenatal care and proactive health measures for pregnant women affected by COVID-19.